Advanced practice profiles and work activities of nurse navigators: An early-stage evaluation. Issue 1 (February 2019) - Spooner, Amy J.; Booth, Natasha; Downer, Tai-Rae; Gordon, Louisa; Hudson, Adrienne P.; Bradford, Natalie K.; O'Donnell, Chris; Geary, Alanna; Henderson, Robyn; Franks, Cherie; Conway, Aaron; Yates, Patsy; et al.
Abstract: Background: Effective coordination and integration of care between health care providers is critical to manage complex, chronic medical conditions. Aim: Describe the advanced practice profile and activities of nurse navigators who provide a service for patients with chronic health conditions. Design: An observational study was conducted in four health services, in Queensland, Australia. Methods: In part one, nurse navigators completed a survey incorporating the Advanced Practice Role Delineation tool. In part two, nurse navigators completed a work activity diary, capturing the time spent performing daily activities, modes of communication and referral sources. Findings: Twenty-three and 18 nurse navigators participated in the survey and diary, respectively. Participants were experienced nurses, working full-time. Participants reported spending a great extent of time performing direct comprehensive care, support of systems and e ducation in surveys. The diaries captured a mean of 20 working days per participant, a total of 5, 748 work activities. including care of 615 patients. The majority of nurse navigator activities were performed within the direct comprehensive care domain. Communication predominantly occurred with patients, families, hospital health professionals either in person, at a healthcare facility or via phone. Discussion: Our research identified three focus areas of nurse navigator activities: direct comprehensive care, support of systems and education . Further work is required to extend the nurse navigators' unique contribution to research and publication and professional leadership. Conclusions: This study established baseline knowledge regarding advanced practice profiles and work activities of nurse navigators, which can be utilised to improve current processes and future enhancement of the role.